PERAN PENYIDIK DALAM MENGUNGKAP TINDAK PIDANA PENGALIHAN OBJEK JAMINAN FIDUSIA (Studi di Polres Kediri) - Kurniawan, Candra Surya; Nurbaedah, Nurbaedah (MIZAN, Jurnal Ilmu Hukum, 2023)
This research, if in the process of investigation activities are slow to complete, then this is contrary to the Chief of Police Regulation Number 6 of 2019 concerning Investigation of Criminal Acts and the Chief of Police Regulation No. 12 of 2009 concerning Supervision and Control of the Handling of Criminal Cases within the Republic of Indonesia Police, article 31 which regulates the time limit for examining and settling cases, namely 120 days for investigations of very difficult cases, 90 days for investigations of difficult cases, 60 days for investigations of medium cases, 30 day for easy case investigations. For this reason, regarding this issue we as writers are interested in conducting legal research entitled The Role of Investigators in uncovering criminal acts of transferring fiduciary objects (Studies at the Kediri Police) with the formulation of the problem The Role of Investigators in Revealing the Crime of Transferring Collateral Objects Fiduciary and investigators' obstacles in uncovering cases of transfer of fiduciary guarantee objects. This type of research uses empirical research with interviews. Data collection techniques use books, legislation, decisions, the internet, and journals. Data analysis techniques use inductive methods to take problems and conclusions obtained from the field. The results of this study in the Role of Investigators in Exposing the Crime of Diversion of Fiduciary Guarantee Objects in the process of investigation and investigation are as follows: Summons, Arrests, Detentions, Confiscations, Examinations. Investigators' obstacles in disclosing cases of transferring fiduciary objects are as follows: The suspect was not present during the investigation process, lost evidence; Investigators cannot detain perpetrators of crimes if they use Article 36 of Law number 42 of 1999 concerning fiduciary guarantees so investigators apply Article 372 of the Criminal Code because in fact the elements in Article 372 of the Criminal Code and Article 36 of Law Number 42 of 1999 are the same, for the investigator applies Article 372 of the Criminal Code to the suspect so that investigators can restrain the suspect; The suspect loses evidence, thus making investigators slow in handling the case and unable to make an arrest. Eliminating evidence makes the object difficult to find